Natural Surfactants and Their Applications for Heavy Oil Removal in Industry. Issue 4 (2nd October 2019) - Rocha e Silva, Nathalia Maria P.; Meira, Hugo M.; Almeida, Fabíola Carolina G.; Soares da Silva, Rita de Cássia F.; Almeida, Darne G.; Luna, Juliana M.; Rufino, Raquel D.; Santos, Valdemir A.; Sarubbo, Leonie A.
Abstract : The cleaning of machinery, petroleum storage tanks and equipment leads to the accumulation of petroleum products in the environment. The removal of grease adhered to motors is a specific challenge. Cleaning processes require direct application of surfactants or solvents, which most often generate further environmental problems due to the accumulation of these toxic substances. The majority of available surfactants are synthesized from petroleum derivatives. However, environmental laws have motivated the development of natural surfactants as an alternative to existing products. Biosurfactants can be obtained from microorganisms and plants. Biodegradable detergents can also be obtained through chemical synthesis. This review presents different alternatives for obtaining biodetergents as well as their industrial applications for the removal of heavy oils and the reduction of cleaning and labor costs in industries.